2020
DOI: 10.33545/surgery.2020.v4.i3e.514
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the prevalence and risk factors of inguinal hernia

Abstract: Background: Hernia is a protrusion of any viscous from its proper cavity. Inguinal hernias being more frequent. The present study was conducted to assess the prevalence and risk factors of inguinal hernia. The present study was conducted to assess the prevalence and risk factors of inguinal hernia. Material and methods: The present study was carried out among 320 adults who had come to the surgery outpatient department for inguinal hernia repair or recurrence over the period of 2 years. The demographic details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A hernia in the abdominal wall can be congenital, meaning that the abdominal wall does not close properly or is acquired [ 5 ]. Numerous factors and causes are associated with hernias, including pre-existing weakness of abdominal muscles, smoking, prior surgeries, and increased intra-abdominal pressure such as obesity, coughing, straining, heavy lifting, and pregnancy [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A hernia in the abdominal wall can be congenital, meaning that the abdominal wall does not close properly or is acquired [ 5 ]. Numerous factors and causes are associated with hernias, including pre-existing weakness of abdominal muscles, smoking, prior surgeries, and increased intra-abdominal pressure such as obesity, coughing, straining, heavy lifting, and pregnancy [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Femoral hernias comprise only 3% of all groin hernias. Indirect inguinal hernia and femoral hernia occur more commonly on the right side [9] A study in Pakistan revealed that inguinal hernias were more prevalent (70%), than paraumbilical hernia (14.5%), umbilical hernia (8.2%) and incisional hernia (7.3%) [10]. A study noted that umbilical hernias were found in 10.2%, groin hernias in 8.3%, incisional in 2.4% of residents; and 30% had undergone hernia repair before [6].…”
Section: Introductionmentioning
confidence: 99%
“…Inguinal hernias are very frequent among men, which account 75% of abdominal wall hernias, with a lifetime risk of 27% for men and 3% for women [3]. Other common sites of abdominal wall hernias include groin, umbilicus, Linea Alba, semilunar line of Spiegel, diaphragm, and surgical incisions [4]. It is estimated that more than 20 million hernias are repaired each year worldwide [5].…”
Section: Introductionmentioning
confidence: 99%